Cognitive-Behavioral Group Therapy and its Effectiveness on Anxiety, Depression, and Anger Caused by Trauma in Injured Athletes - Seyedeh Samira Hoseini; Hassan Gharayagh Zandi; Fazlallah Bagherzadeh; Azam Noferesti (University of Tehran, 2024)
Introduction: Sports injuries are often associated with emotional and psychological challenges. Psychologists and team physicians should examine emotional reactions in addition to assessing physical factors. This research aimed to investigate the effectiveness of cognitive-behavioral group therapy on anxiety, depression, and anger caused by the psychological trauma of injury in injured athletes.Methods: The statistical sample of the research was 32 professional athletes injured due to psychological trauma who were selected conveniently, purposively, and with the approval of the experts from the Sports Medicine Federation. The athletes were randomly assigned into two groups of 16 people consisting of a treatment group and a control group. After applying the treatment, a post-test and a two-month follow-up test were conducted. The measurement tools in this research were Spielberger's State-Trait Anger Expression Inventory-2 (STAXI-2), Beck Anxiety Inventory (BAI), and Beck Depression Inventory - Second Edition (BDI-II). The data were analyzed using the repeated measures analysis of variance statistical method (P<0.05).Results: The results showed that the difference between the experimental and control groups in reducing behavioral problems in the post-test and follow-up phase was significant. The follow-up results after two months also showed that there was a difference between the experimental and control groups in the amount of psychological reactions and the effectiveness of the treatment remained after 2 months.Conclusion: The results indicated that cognitive-behavioral therapy focused on psychological trauma reduces the psychological problems of athletes such as anxiety and depression, but does not affect anger control.